Chiari Type 1 malformation: A case report (Indian Journal of Case Reports, 2024)
Type I Chiari malformation (CM) is an acquired or congenital disorder characterized by herniation of the cerebellar tonsils through the foramen magnum and into the spinal canal. The resulting anatomic abnormality impairs the flow of cerebral spinal fluid and results in the Chiari symptoms and signs. The purpose of this study was to report a case of successfully treated CM Type 1 that was discovered accidentally during childhood. A 9-year-old female presented to the emergency department complaining of dizziness and headache. Before her admission, she lost balance and collapsed to the ground fainting. A magnetic resonance imaging (MRI) scan of the brain disclosed herniation of cerebellar tonsils through the foramen magnum at 13 mm below the spinal canal. It is very difficult to determine the true frequency of this disorder early in childhood. A definitive diagnosis is generally made after a MRI, where the abnormal protrusion of the cerebellum toward the spinal cord can be seen.